Genotypic study of Tunisian Arabian stallions - Jlassi, Mariam; Jemmali, Bayrem; Ahmed, Hatem Ouled; Lasfer, Faten; Gara, Aberrahmene Ben (Acta Biologica Szegediensis, 2022)
Diversity of Arabian stallions distributed throughout the territory of Tunisia has been evaluated. Seventeen microsatellite markers were used for the determination of genetic variation. A total of 95 alleles were detected in the 50 stallions studied. The number of alleles per locus ranged from 2 to 9 with an average of 5.6. The observed mean number of genetically diverse alleles (Na) was 5.6 (0.44). The mean number of expected alleles (Ne) was 3.42 (0.28). The average expected and observed heterozygosity was approximately 0.675 (0.026) and 0.593 (0.044), respectively. Principal component analysis showed the presence of 2 subpopulations in the studied sample set. These findings demonstrate the potential of microsatellites as a tool for designing and controlling animal breeds. Results show that the population under study has sufficient levels of genetic variations, which can be used as a foundation for developing plans for species conservation and long-term sustainability.